2005
DOI: 10.1002/jcp.20519
|View full text |Cite
|
Sign up to set email alerts
|

Stable knockdown of CFTR establishes a role for the channel in P2Y receptor‐stimulated anion secretion

Abstract: P2Y receptor regulation of anion secretion was investigated in porcine endometrial gland (PEG) epithelial cells. P2Y2, P2Y4, and P2Y6 receptors were detected in monolayers of PEG cells and immunocytochemistry indicated that P2Y4 receptors were located in the apical membrane. Apical membrane current measurements showed that Ca2+-dependent and PKC-dependent Cl- channels were activated following treatment with uridine triphosphate (UTP) (5 microM). Current-voltage relationships comparing calcium-dependent and PKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 77 publications
2
31
0
Order By: Relevance
“…This finding suggests the possibility that genistein may stimulate Cl - secretion directly via CFTR as has been reported by others [17,20]. Although UTP has been shown to activate CFTR [34,38], it is likely that the UTP-induced transient increase in I sc could be a result of the stimulation of Cl - secretion, primarily through Ca 2+ -activated Cl - channels. Apart from a direct interaction with CFTR, genistein may increase CFTR localization in the plasma membrane [25,26].…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…This finding suggests the possibility that genistein may stimulate Cl - secretion directly via CFTR as has been reported by others [17,20]. Although UTP has been shown to activate CFTR [34,38], it is likely that the UTP-induced transient increase in I sc could be a result of the stimulation of Cl - secretion, primarily through Ca 2+ -activated Cl - channels. Apart from a direct interaction with CFTR, genistein may increase CFTR localization in the plasma membrane [25,26].…”
Section: Discussionmentioning
confidence: 42%
“…Previous studies done on porcine endometrial epithelial cells have reported that UTP activates Cl - secretion via an increase in the intracellular Ca 2+ and in PKC stimulation [33,34]. We further examined the effects of genistein in the presence of UTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal human bronchial epithelial cells (NHBE) purchased from Lonza (Allendale, NJ) were passage extended by transfection with the catalytic subunit of human telomerase as previously described (32,33). NHBE cells were maintained in complete bronchial epithelial growth media (bronchial epithelial basal medium ϩ BEGM Bullet Kit).…”
Section: Cell Culturementioning
confidence: 99%
“…CFTR was silenced in Calu-3 cells using the Sleeping Beauty transposon vectors pT2/si-PuroV2 for short hairpin RNA (shRNA) expression as previously described (32,33). Positive transfectancts were selected using puromycin (4 g/ml).…”
Section: Cftr Shrna Silencingmentioning
confidence: 99%